Financial literacy in tourism and management & business administration entry-level students: A comparative view - Arquero, José L.; Fernández-Polvillo, Carmen; Jiménez-Cardoso, Sergio M. (The journal of hospitality, leisure, sport & tourism education, 2024)
Financial competences are essential in the tourism industry and consequently are valued in hiring and promotion decisions. However, according to the literature, tourism graduates appear to have inadequate levels of financial skills. The perceived lack of required competences results in a competitive disadvantage for tourism graduates in favour of those who studied Management & Business Administration, or equivalent degrees. To explain this gap, some authors point to the scarcity of finance-related courses within the curriculum of most of tourism or hospitality programs, but it is also suggested that the characteristics of the students enrolling in tourism and hospitality degrees could play a relevant role, highlighting that those students lack the required background knowledge and attitudes resulting in major constraints for financial competences development. Our study compares the levels of financial literacy, financial self-efficacy, numeracy, and financial interest of entry-level students enrolled in these two competing university degrees, Tourism and Management & Business Administration. Our results indicate significant differences in both variables that in addition to the scarcity of finance subjects in the tourism curriculum could affect the students’ prospects and employability. •Financial competences are highly relevant for professional success in tourism firms.•Managers are sought among MBA graduates due to a perceived lack of required competences.•The lower levels of financial literacy, and interest point to a self-selection bias.•Their departing position is less favourable to develop the desired financial skills.